2019
DOI: 10.1101/723312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutrient-dependent mTORC1 signaling in coral-algal symbiosis

Abstract: To coordinate development and growth with nutrient availability, animals must sense nutrients and acquire food from the environment once energy is depleted. A notable exception are reef-building corals that form a stable symbiosis with intracellular photosynthetic dinoflagellates (family Symbiodiniaceae (LaJeunesse et al., 2018)). Symbionts reside in 'symbiosomes' and transfer key nutrients to support nutrition and growth of their coral host in nutrient-poor environments (Muscatine, 1990;Yellowlees et al., 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…2a, Fig. S2b) (Voss et al, 2019). In contrast, M. gaditanacontaining cells are basically indistinguishable at the transcriptional level from aposymbiotic cells ( Fig.…”
Section: Symbiosis Establishment Broadly Suppresses Host Cell Immunitmentioning
confidence: 85%
See 4 more Smart Citations
“…2a, Fig. S2b) (Voss et al, 2019). In contrast, M. gaditanacontaining cells are basically indistinguishable at the transcriptional level from aposymbiotic cells ( Fig.…”
Section: Symbiosis Establishment Broadly Suppresses Host Cell Immunitmentioning
confidence: 85%
“…RNA sequencing data from Voss, et al (2019) results was restricted to pathways involved in innate immunity as found in KEGG (Kanehisa and Goto, 2000), using the R! package "ComplexHeatmap" (Gu et al, 2016) in KNIME (Berthold et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations